DESIGN AND BUILD OF A DC MOTOR CONTROL TRAINER BASED ON A PROGRAMMABLE LOGIC CONTROLLER USING RESEARCH AND DEVELOPMENT METHODS: RANCANG BANGUN TRAINER KENDALI MOTOR DC BERBASIS PROGRAMMABLE LOGIC CONTROLLER DENGAN METODE RESEARCH AND DEVELOPMENT - Zarkasyi, Ach; Haryanto; Rahmawati, Diana (UPMI Proceeding Series, 2023)
The aims of this research are (1)needs analysis; (2)get results; (3) know the performance; and (4)know the feasibility about development of trainer for DC (Direct Current) motor speed control based on Programmable Logic Controllers (PLC) for laboratory work for Electrical Engineering Undergraduate Study Programs at University of Trunojoyo Madura. The development of trainer is refer to a research and development method, which have research steps: a)the defining step, in the form of initial to final analysis, student analysis, concept analysis, task analysis, goal analysis, and results; b)the planning step (Design), in the form of simulator design; c)Development step (Development) in the form of validation, practicality, and effectiveness tests using simulators; and d)Disseminate step in the form of the dissemination step of the simulator that has been developed. The results showed that: (1) The needs chosen by the most respondents in PLC practice are: (a) PLC-based DC motor speed control trainer; (b) PLC practice module; and (c) The required trainer kit criteria include: according to competence, size according to standards, made of good components; and refers to work safety; (2) A PLC-based trainer kit has been produced in the form of simulation of DC motor speed control; (3) PLC-based products have good performance, which is shown that 100% of the components can work properly, and all job descriptions (100%) of the trainer kits can work as their function; and (4) PLC-based trainer products are very suitable for PLC practice, which is shown by the validation of material experts giving a score of 89.42% (very feasible), and students give assessment with a score of 86,16% (very feasible).